EFFECTIVENESS OF ORAL HEALTH EDUCATION INTERVENTION AMONG ADULT POPULATION VISITING PRIVATE DENTAL COLLEGE - Santa Packyanathan, Jerusha; P, Jayashri; Jeevanandan, Ganesh (International Journal of Psychosocial Rehabilitation, 2025)
Oral hygiene is very important in maintaining good oral health. Lack of patient education is the main cause for bad oral hygiene and leads to multiple oral problems the most common being caries and periodontal diseases. Therefore health literacy is a vital part of every dental appointment not only to educate but also reinforce good oral habits and prevent further advancement of a disease. The main aim of the study is to examine the effectiveness of oral health education intervention among the adult population visiting Private dental college. This is a record based study with a sample size of 618, irrespective of the gender. The study was conducted at the institution and the data was collected from the patient records. The data was categorised into age groups, gender and plaque index scores recorded before and after oral health education. Assessment of Plaque using Plaque Index (Silness and Loe; 1964). Plaque index was recorded for the Indexed teeth (16, 12, 24, 36, 32, 44) prior to oral prophylaxis with the help of plaque test disclosing solution. The coding was done in MS excel. The data was transferred to a host computer and processed using SPSS software version 21.0 (SPSS Inc., Chicago, IL, USA) by tabulation and graphical illustration. Plaque index scores were continuous variables. Hence, it was presented as mean and standard deviation values. Paired T test was used to compare the mean differences of Plaque Index (Before and after health education Mean Plaque scores). One way ANOVA was used to find the difference between the different age groups with respect to mean pre-plaque index. Independent T test was used to find the difference between the gender with respect to the mean pre-plaque index. The plaque index score before and after the oral health education intervention were compared using one way Paired T -Test. The average plaque index score before health education was 1.4 with standard deviation of 0.36 and the average plaque index score after health education was 0.5 with standard deviation of 0.14. The results obtained were highly statistically significant (P value = 0.001).Based on the results of the present study, we can conclude that the mean Plaque Index score has been significantly reduced after oral health education intervention among the study subjects enrolled in the research.